The role of media in sponsorship decision making during Covid-19 : a Malaysian perspective - Mohamad-Noor Salehhuddin Sharipudin,; Nurzihan Hassim,; Suffian Hadi Ayub,; Fam, Kim-Shyan; Rosli Mohammed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
COVID-19 has impacted not only human lives, but also business organisations. The repercussions of the pandemic on global businesses include sustaining the value of a firm that could benefit stakeholders, such as the challenge for sponsored properties to attain sponsorship through a period of financial struggles and the capacity of a sponsor to provide it. It is imperative for business-to-business (B2B) communities to evaluate criteria and risks of sponsorship to instil public trust and consequently result in value creation for firms. At the same time, the role of the media is pivotal to create visibility of this partnership and achieve set sponsorship aims. With that said, the objective of this study is to explore the role of sponsorship decision making by Malaysian organisations during the pandemic and how the media have strengthened relationship marketing between businesses and their stakeholders; by examining the determinant factors of using media as an activation in sponsorship and the criteria of using media in sponsorship. The qualitative study conducted interviews with 13 corporate communication and marketing managers in Malaysia that are involved directly with sponsorship activation. The findings highlight the sponsorship ecosystem through the Malaysian media and B2B perspectives that would guide practitioners in making strategic decisions on B2B sponsorship matters, particularly on the relational approaches and media engagement should be seen as part of good business conduct. Future recommendation of this research is to seek the perceptions of consumers on the congruence of relationship marketing through sponsor-sponsored properties collaboration in Malaysian media.